2022
DOI: 10.1097/md.0000000000027743
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of acupuncture on gut microbiota in participants with subjective cognitive decline

Abstract: A close relationship has recently been described between subjective cognitive decline (SCD) and gut microbiota disorders. Herein, we aim to investigate the effect of electroacupuncture (EA) on gut microbiota in participants with SCD.We conducted a study of 60 participants with SCD. Sixty participants were allocated to either EA group (n = 30) or sham acupuncture group (n = 30). Both groups received 24 sessions of real acupuncture treatment or identical treatment sessions using the placebo needle. Global cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…These findings confirmed, for the first time, that MA could effectively regulate the gut microbiota disorder and restore the normal microbiota structure in APP/PS1 mice, as reflected in the downregulation of Proteobacteria and Escherichia-Shigella , as well as the upregulation of Bacteroidetes, and the effect was comparable to that of probiotics. Previous studies have shown that acupuncture can protect the gut microbiota by promoting the growth of Lactobacillus and Bifidobacterium and inhibiting the proliferation of Bacteroides fragilis and Enterococcus , thereby exerting a therapeutic effect on many diseases such as depression and ulcerative colitis ( Savari et al, 2014 ; Ma et al, 2019 ; Hong et al, 2020 ; Liu G. H. et al, 2020 ; Song et al, 2020 ; Wang et al, 2022 ). However, MA showed no significant regulation of the aforementioned flora in our study, which we speculated might be related to the existence of characteristic flora disorders in different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirmed, for the first time, that MA could effectively regulate the gut microbiota disorder and restore the normal microbiota structure in APP/PS1 mice, as reflected in the downregulation of Proteobacteria and Escherichia-Shigella , as well as the upregulation of Bacteroidetes, and the effect was comparable to that of probiotics. Previous studies have shown that acupuncture can protect the gut microbiota by promoting the growth of Lactobacillus and Bifidobacterium and inhibiting the proliferation of Bacteroides fragilis and Enterococcus , thereby exerting a therapeutic effect on many diseases such as depression and ulcerative colitis ( Savari et al, 2014 ; Ma et al, 2019 ; Hong et al, 2020 ; Liu G. H. et al, 2020 ; Song et al, 2020 ; Wang et al, 2022 ). However, MA showed no significant regulation of the aforementioned flora in our study, which we speculated might be related to the existence of characteristic flora disorders in different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies on the gut microbiota and acupuncture are lacking, the discovery of the partial relief of dysbiosis in the gut microbiome in MCI by acupuncture [ 24 ] has aroused great interest among researchers. Additionally, genetic markers that predict the progression of MCI are needed so that interventions to prevent AD development can be implemented.…”
Section: Introductionmentioning
confidence: 99%
“…However, the interaction between gut microbiota and acupuncture treatment has been scarcely investigated. Only one clinical study ( Wang et al, 2022 ) have revealed that dysbiosis was found in the gut microbiome in subjective cognitive decline and partially relieved by acupuncture, Bifidobacterium is positively correlated with clinical efficacy Z-score and Montreal Cognitive Assessment (MoCA) Scale (both P < 0.005). Additionally, it is necessary to conduct systematic research on MCI elderly people to explore the prevention strategy of AD in the future, which can not only understand the evolution process of intestinal flora during and after acupuncture but also provide the basis for making the prevention plan for early cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%